THE APPLICATION OF THE SIX SIGMA METHOD IN REDUCING QUALITY FAILURE COSTS A CASE STUDY IN A DIWANIYAH TEXTILE FACTORY - M.D. Khawla Radi Athab; Hayder Hamzah Saleeh; Dr. Laith Ali Muttar (American Journals Publishing, 2023)
Companies work in light of changes and environmental challenges represented by intense competition between various industrial companies, and the quality of products and services provided to customers is a basic issue that all companies focus on to ensure their success and continuity, in providing products to customers according to their desires, specifications and prices that they want to pay for their acquisition and to ensure their survival in market. This research aims to measure the impact of the application of the six sigma method in industrial companies and to indicate the extent of its contribution to reducing the costs of quality failure. Prepared by the researcher, as for the second axis, it included six sigma criteria as a major variable consisting of four sub-axes (commitment and support of senior management, continuous improvement, human resources, focus on customers), and the paragraphs were formulated based on the scale (Yang, 2010). While the third axis included the costs of quality failure as a major variable consisting of four sub-axes (preventive costs, evaluation costs, internal failure costs, external failure costs) the paragraphs were formulated based on a scale (Hamouda, 2014). Departments of the lab, Diwaniyah tissue, the research sample, and only 50 forms were retrieved, and the descriptive analytical method was relied on in the research, in addition to conducting interviews with a number of department managers in the lab p soft search. For the purpose of analyzing the collected data, some statistical methods were used, such as the arithmetic mean, standard deviation, coefficient of variation, simple correlation coefficient and impact analysis. A set of conclusions has been reached, the most important of which is the presence of many difficulties that limit the ability to apply the six sigma method.
Keywords: six sigma, quality, quality failure costs